A facile design of thio-perylenediimides with controllable fluorescent, photodynamic and photothermal effects towards cancer theranostics. Issue 97 (22nd November 2021) - Liu, Chang; Ji, Chendong; Fan, Zongyang; Ma, Ruihao; Yin, Meizhen
Abstract : A series of thionated perylenediimides with controllable fluorescent, photodynamic and photothermal effects have been synthesized by a one-pot method for multiple cancer phototheranostics. Abstract : A series of thionated perylenediimides with modulating phototheranostic modalities have been synthesized by a one-pot method for multiple anti-cancer applications. Compared to the initial and 4- tert -butyl phenol-substituted fluorescent perylenediimide, the obtained monothionated perylenediimide became photodynamic. With the increase of thionation degree, tetrathionated perylenediimide changed into an optimal photothermal agent.